Molecular Bases of Sleep - Rojas-Jaimes, Jesús (2023)
Sleep is vital for all mammals including humans, its distortion implies different health risks and pathologies such as depression, and cardiovascular diseases, and in the end, it can lead to death. In this sense, it is important to find the molecular bases of sleep, among them the genes and their proteins that play a key role in the homeostasis of the living being. Information was collected using the PubMed/Scopus databases in English with a 10-year history using the PICO methodology to determine the words P=Genes, I=Molecular basis, C=Not applicable, O=Sleep. Original articles were determined into two large groups, among these are the "Clock Genes" and other "Genes and Proteins" related to sleep. Among the important clock genes identified are those linked to dopamine (DRD 2) and (DAT 1) and other genes such as pdm3 that participate in the genesis of the innervation of the dopaminergic system and the ANXA3 and 17GAM genes which has shown that overexpression of these is related to sleep deprivation. Understanding the molecular bases of sleep and its gaps still to be studied are key to future studies such as identifying targets and drugs to treat sleep disorders.